Pursuing Legal Harmony: Indonesianization of Islamic Law Concept and Its Impact on National Law - Suud Sarim Karimullah (Fakultas Syariah UINSI Samarinda, 2022)
This study responds to a polemic on Indonesia’s formalization of Islamic law, which is inseparable from the dynamics of political authority and the internal views of Muslims. It seeks to describe, explore, construct, and analyze the ​​Indonesianization of Islamic law, as proposed by Kamsi, an Islamic law professor at Sunan Kalijaga State Islamic University of Yogyakarta, as one of the efforts to make Islamic law become the national law. The Indonesianization of Islamic law, namely by legislating or codifying Islamic law through the state system so that it is enforceable in Indonesia. This study is conceptual research using a legal philosophy approach to comprehend an Islamic legal thought from a sharia scholar using the content analysis method. The results of this study show that the concept of Indonesianisation of Islamic Law uses a modern knowledge system as the paradigm. This effort seeks to nationally legalize Islamic law through Indonesian legal instruments that can give birth to inclusiveness and tolerance coupled with pluralism with differentiation in unification. Its theoretical implication emphasizes a need for epistemological and axiological adjustments to realize the concept of Indonesianization of Islamic law. The idea should also apply nationally within the framework of Pancasila (the Indonesian state’s ideology) as a democratic country. Keywords: Kamsi, Indonesianization of Islamic Law, National Law.